THE ANALYSIS OF PROFIT QUALITY ON BANKING INDUSTRY IN THE MOMENT OF SLOWING DOWN ECONOMY - Ridwan Nurazi; Intan Zoraya (Jurnal Bisnis Tani, 2016)
In the moment of slowing down economy, the banking sector faces severe challenges, mainly due to the impact of the weakening of the rupiah against the US dollar. This study aimed to analyze the effect of earnings quality, managerial efficiency, and the persistency of earnings to the banking index. The object of this study is the five largest banks in Indonesia, namely: Bank Mandiri, Bank Rakyat Indonesia, Bank Central Asia, Bank Negara Indonesia and Bank Danamon. The five banks are benchmarks for the national banking industry. The method used is the data panel analysis regression. The results shows that the quality of earnings, managerial efficiency, and the persistence of earnings affect amounted 35.9137% on the banking indexes; the remaining amount of 64.0863% influenced by macroeconomic factors. The most severe impact surged on the Bank Danamon, while the lightest impact occurred on Bank Rakyat Indonesia.